PENGEMBANGAN SISTEM INFORMASI KEPENDUDUKAN DI DESA KALENSARI KECAMATAN COMPRENG - Hirawan, Zaenal (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Kalensari Village is one of the villages in Compreng District, Subang Regency, which has the potential for development in the field of digitalization, especially related to village population data management. This is based on the population registration process which still uses manual books or conventional archives. This model, of course, still experiences obstacles in the process of updating data in real time, is vulnerable to file loss, and ultimately hampers the decision-making process. This condition prompted a team of lecturers and students to plan the development of a simple population information system that assists village officials in updating resident population data. Because in the digital era like today, the need for an integrated information system is becoming increasingly important. A digital population information system can help villages manage population data more efficiently, securely, and easily accessed. In addition, digitalization also simplifies administrative services for the community, accelerates the reporting process, and supports transparency in village data management. This information system can be accessed by village officials in carrying out service duties to the community as a form of fast, accurate, cheap service and supports technology-based village development